EMMPRIN deficiency alleviated metabolic-associated steatohepatitis progression via regulation of the UBA52–MCT1 axis - Lai, Linying; Huang, Baoyuan; Song, Ziping; Zhu, Xinyan; Yang, Wenzhuo (Frontiers in Pharmacology, 2026)
BackgroundMetabolic dysfunction-associated steatohepatitis (MASH) is characterized by a lipid overload-induced pathological cascade featuring hepatocyte injury, inflammation, and progressive fibrosis. This study aims to systematically investigate the role of EMMPRIN in MASH progression, and to elucidate its mechanisms in reprogramming the hepatic metabolic microenvironment.MethodsMurine models induced by methionine-choline -deficient diet, hepatocyte-specific EMMPRIN overexpression and knockout mice models were used to evaluate EMMPRIN’ roles in steatohepatitis. Parallel in vitro studies were conducted in corresponding cellular models. Proteomic sequencing, mass spectrometry, co-immunoprecipitation, Western blotting, quantitative PCR, and immunofluorescence were employed to identify downstream targets and characterize ubiquitination modifications.ResultsEMMPRIN overexpression significantly exacerbated MASH phenotypes, including hepatic steatosis, inflammatory infiltration, and collagen deposition. Conversely, EMMPRIN knockout conferred substantial protection against these pathological changes both in vivo and in vitro. Mechanistically, EMMPRIN downregulated UBA52 expression, resulting in reduction in the free ubiquitin pool and subsequent decrease in K63-linked polyubiquitination of monocarboxylate transporter 1 (MCT1). This ubiquitination defect led to destabilization of MCT1 and was associated with a global increase in protein lactylation in EMMPRIN-deficient models. Furthermore, EMMPRIN suppression inhibited several signaling pathways critically involved in MASH pathogenesis, including PPAR signaling, Notch signaling, and TGF-β-mediated fibrotic response.ConclusionOur findings demonstrate that EMMPRIN promotes MASH progression through the UBA52-MCT1 regulatory axis, which modulated ubiquitin-dependent protein stability and induced metabolic reprogramming, thereby driving lipid accumulation, inflammation, and fibrosis. These results position EMMPRIN as a promising therapeutic target for MASH intervention.